A 2D magnetic and 3D mechanical coupled finite element model for the study of the dynamic vibrations in the stator of induction motors. (January 2016) - Martinez, J.; Belahcen, A.; Detoni, J.G.
Abstract: This paper presents a coupled Finite Element Model in order to study the vibrations in induction motors under steady-state. The model utilizes a weak coupling strategy between both magnetic and elastodynamic fields on the structure. Firstly, the problem solves the magnetic vector potential in an axial cut and secondly the former solution is coupled to a three dimensional model of the stator. The coupling is performed using projection based algorithms between the computed magnetic solution and the three-dimensional mesh. The three-dimensional model of the stator includes both end-windings and end-shields in order to give a realistic picture of the motor. The present model is validated using two steps. Firstly, a modal analysis hammer test is used to validate the material characteristic of this complex structure and secondly an array of accelerometer sensors is used in order to study the rotating waves using multi-dimensional spectral techniques. The analysis of the radial vibrations presented in this paper firstly concludes that slot harmonic components are visible when the motor is loaded. Secondly, the multidimensional spectrum presents the most relevant mechanical waves on the stator such as the ones produced by the space harmonics or the saturation of the iron core. The direct retrieval of the wave-number in a multi-dimensional spectrum is able to show the internal current distribution in a non-intrusive way. Experimental results for healthy induction motors are showing mechanical imbalances in a multi-dimensional spectrum in a more straightforward form. Abstract : Highlights: A 2D electromagnetic and 3D mechanical model has successfully coupled to study the steady-state vibrations of an induction motor. The validation has been done by means of using an array of accelerometers on the periphery of the stator offers a better picture of the inner current distribution of the motor. The load conditions of the motor is important since radial vibrations have higher components due to the so-called slot harmonics. Using an array of accelerometers together with multi-dimensional spectral analysis allows to classify waves according to their phase velocity.